Vulnerability assessment of drinking water supply under climate uncertainty using a river contamination risk (RANK) model. (April 2022) - Behzadi, Faranak; Wasti, Asphota; Steissberg, Todd E.; Ray, Patrick A.
Abstract: A river contamination risk (RANK) framework is developed to demonstrate the application of a Computational Fluid Dynamics model in risk assessment of contamination exposure in surface waters. The ultimate goal is to identify the factors responsible for potential future river contamination emergencies, and the use of that insight to inform strategic investments in resilience-enhancing infrastructure and policies. The RANK model is applied to preliminary assessment of a historical contamination event in the Ohio River. The results prove that with higher river velocity, plume passage becomes faster, with earlier peak time and shorter duration of plume at the point-of-interest. For the case under study, with increasing the initial spill duration by 100%, the plume duration at the point-of-interest may increase 85% or 65% depending on the toxicity level of the contaminant. The sensitivity analysis on hydraulic inputs implies that RANK can be utilized for climate-informed decision analysis in water quality applications. Highlights: RANK allows for variable channel width, water depth, and velocity leading to accurate results. RANK considers uncertainty of climate, pollution source, and infrastructure operations. RANK is tuned for stress testing on water contamination and water supply interruption. RANK is suited for climate change risk assessments to evaluate the water quality impacts.